Exploring the potential of laser capture microdissection technology in integrated oral biosciences. (26th September 2016) - Thennavan, A; Sharma, M; Chandrashekar, C; Hunter, K; Radhakrishnan, R
Abstract : Laser capture microdissection (LCM) is a high‐end research and diagnostic technology that helps in obtaining pure cell populations for the purpose of cell‐ or lesion‐specific genomic and proteomic analysis. Literature search on the application of LCM in oral tissues was made through PubMed. There is ample evidence to substantiate the utility of LCM in understanding the underlying molecular mechanism involving an array of oral physiological and pathological processes, including odontogenesis, taste perception, eruptive tooth movement, oral microbes, and cancers of the mouth and jaw tumors. This review is aimed at exploring the potential application of LCM in oral tissues as a high‐throughput tool for integrated oral sciences. The indispensable application of LCM in the construction of lesion‐specific genomic libraries with emphasis on some of the novel molecular markers thus discovered is also highlighted.